Perkembangan Konsep Pemasaran: Implementasi dan Implikasinya - Ambar Lukitaningsih (Universitas Proklamasi 45 Yogyakarta, 2013)
Writing paper is conducted to reveal the development of the marketing concept, implementation and implications. The explanation begins with a description of the scope of marketing, a second discussion about the marketing concept and its development, followed by a discussion of the implementation of the marketing concept and concludes with managerial implications. The development of the original understanding of marketing is more focused issue of physical distribution business enterprise then develop to the transaction which although not involve spending money and marketing activities can be carried out by institutions outside the business. As a consequence of the expansion of the notion of marketing, the scope of marketing is also increasingly widespread. This process continues so that raises more and more marketing phenomenon. Phenomena are analyzed and presented by marketing experts, is then used as a reference in understanding the implementation of the marketing concept between the years 1960-1980’s. Changes have occurred with the theory of alternative marketing concept proposed by Fullerton (1988) and Houston (1986). In terms of the marketing concept, which originally seated over the company as the first and last of a series of business activities, changed completely to the consumer as the beginning and end of the company’s activities. The development of the role of marketing revealed by Webster (1992) provides the latest alternative marketing concept that acts as an organizational network. Logical consequence all company activities should be directed to the consumer, given the conditions of competition has increased, but in doing its work, the company should be prosecuted execute better than its competitors in order eventually to provide customer satisfaction and this is the purpose of the company.